Investigations on NiTi shape memory alloy thin wall structures through laser marking assisted wire arc based additive manufacturing. (June 2021) - Singh, Shalini; Resnina, N.; Belyaev, S.; Jinoop, A.N.; Shukla, Ashish; Palani, I.A.; Paul, C.P.; Bindra, K.S.
Abstract: Micro Electro Mechanical System (MEMS) devices require thin Shape Memory Alloy (SMA) structures for actuator and vibration damper applications. However, fabricating customized SMA based thin structures are crucial and challenging for specific device requirements using conventional manufacturing. The above issues can be addressed using advanced manufacturing techniques, like - Wire Arc Additive Manufacturing (WAAM) technique. However, fabrication of the thin-wall structures with controlled geometry using WAAM is technically challenging due to melt-pool instability, residual stress, and distortion during fabrication. One of the methods to address the above issues is hybridization of WAAM with pre-surface treatment using Laser-marking. In the present work, the effect of number of laser passes during laser marking is investigated and the deployment of laser-marking treatment before deposition of each WAAM layer reduced the surface roughness (24 μm to 2.8 μm) and surface energy, which reduces the track width. The defects and distortions are successfully eliminated with 2 mm width of marked laser track on which thin section is fabricated. The fabricated samples are systematically investigated using characterization techniques to examine their surface morphological and mechanical properties. Shape Memory recovery of the fabricated sample is also investigated through its actuation characteristics by joule and hot plate heating with maximum achieved displacement of 2.4 mm. Through this technique, feature size of WAAM can be reduced, which will play a significant role in fabrication of complex components with thin structures.